Notions of Nobility in the 16th Century Grand Duchy of Lithuania: Lineage and Virtue - Čižauskas, Karolis (Lietuvos istorijos studijos, 2024)
The aim of this text is two-fold. Firstly, a general view of terminological difficulties arising when attempting to name nobility as a whole is presented with the main issue to be faced is the fact that terms such as ‘bajorija’ (a Lithuanian term) or ‘szlachta’ (a Polish one) simultaneously denote a specific and smaller subclass of nobility. Therefore, the Lithuanian neologism ‘kilnuomenė’ has been presented and introduced. It is justified as etymologically bearing two significant notions which were core to the nobility – that of lineage plus nobleness (by nobility, we mean here a ‘noble’ quality of personality character, a virtue). Secondly, departing from this proposed concept of nobility, a historical enquiry and analysis have been carried out whose main purpose was that of demonstrating how both lineage and nobleness (via virtue) functioned in defining membership in the group and acting as an important element of self-representation.
Keywords: nobility; Grand Duchy of Lithuania; Andreas Volanus; discourse; virtue